Correlation between Calorie Intake and Nutritional Status of Autism Spectrum Disorder in Children - Windaru, Aryo; Veronica, Fifi; Sari, Dian Marta (Althea Medical Journal, 2016)
Background: Autism Spectrum Disorder (ASD) is a severe pervasive developmental disorder with prevalence as high as one in sixty-eight children. Children diagnosed with ASD may have food intake problem and might affect their nutritional status in the future. The objective of this study was to analyze the correlation between total calorie intake and nutritional status of ASD children.Methods: This cross-sectional study was conducted in Indigrow Child Development and Autism Center involving 16 patients from October to November 2015. Total calorie intake was assessed by 24-hour food recall and nutritional status was measured by Z-score. Correlation was analyzed using Spearmanâs Rho. Results: Overweight and obesity were found in 10 out of 16 ASD children assessed. Total calorie intake was not significantly correlated with nutritional status of ASD children (r=0.021, p=0.940).Conclusions: There is no significant relevance between total calorie intake and nutritional status in ASD children at Indigrow Child Development and Autism Center. [AMJ.2016;3(2):320â3]DOI:Â 10.15850/amj.v3n2.790Â